Islamic marketing practices in the cosmetics and toiletries industries in Klang Valley, Malaysia - Kamarohim, Nor Azlina; Bojei, Jamil; Muhammad, Nur Syuhada; Othman, Manisah (Universiti Putra Malaysia Press, 2016)
The purpose of this study is to investigate whether producers, dealers and agents of the Cosmetic and Toiletries Industries in Malaysia are implementing Islamic marketing practices in producing and selling their products. There is growing consciousness to conduct business in accordance to the rules and principles of Islam whereby halal products and services are gaining importance in many industries. The Islamic consumer market is huge and producers are beginning to realise its importance. This study employed the descriptive research method and non-probability sampling technique whereby data were collected through questionnaires distributed to a sample population in Klang Valley. The results show that self and social perspective and marketing scenario to have a significant impact on marketing practices. The study reveals that most of the marketing mix of product and distribution (place) strategy are being practised according to Islamic rules.